The influence of multiple processing on selected properties of a new polymer material based on thermoplastic starch - Moraczewski, Krzysztof; Gozdecki, Cezary; Kociszewski, Marek; Jagodziński, Bartłomiej; Szabliński, Krzysztof; Stepczyńska, Magdalena (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The study discusses the results of research on the multiple processing of thermoplastic starch-based polymer compositions. The research subject was two compositions from the envifill® M product line (Grupa Azoty, Poland): M30 and MB173, intended for injection applications. The materials underwent four processing cycles, each consisting of extrusion and injection operations. The research included determining the mass flow rate, mechanical parameters (tensile strength, bending strength, Young’s modulus, impact strength), thermomechanical parameters (storage modulus as a function of temperature), and thermal parameters (thermal resistance, phase transition temperature). The change in these parameters as a function of the processing rate was examined. It was shown that if one wants to reuse waste from the tested compositions, MB173 turns out to be a better material. Even though in the case of the M30 material, the changes obtained do not disqualify this material for re-use, a greater control of the degree of prior processing and the amount of waste used is recommended.